Evaluation of the fundamental absorption spectrum of a material by its refractive index dispersion in the transparency range - Andriyevsky, B.V.; Romanyuk, M.O.; Romanyuk, G.M. (Functional Materials, 2004)
A method has been elaborated to reconstruct the material absorption spectrum k(ω') in the ranges of fundamental excitations (ω') basing on the refractive index dispersion n(ω) in the material transparency range (ω). The method has been applied to evaluate of the linear dichroism Δk(ω') spectra of K₂Ca(SO₄)₂-H₂O crystals (syngenite) proceeding from its birefringence dispersion Δn(ω). The Δk(ω') spectra of syngenite have been obtained and analyzed for several temperatures in the range of 293 to 450 K for mechanically free and uniaxially pressed (σ = 250 bar) samples. Предложен метод реконструкции спектра поглощения материала k(ω') в областях фундаментальных возбуждений (ω') на основании дисперсии показателя преломления n(ω) в области прозрачности (ω). Метод применен для оценки спектра линейного дихроизма Δk(ω') кристалла K₂Ca(SO₄)₂-H₂O (сингенит) на основании дисперсии двулучепреломления Δn(ω). Полученные спектры Δk(ω') проанализированы для нескольких температур в области 293-450 K для механически ненапряженных и одноосно сжатых (σ = 250 бар) образцов. Запропоновано метод реконструкції спектра поглинання матерiалуk(ω') в областях фундаментальних збуджень (ω') на основі дисперсії показника заломлення n(ω) в області прозорості (ω). Метод застосовано для оцінки спектра лінійного дихроїзму Δk(ω') кристалу K₂Ca(SO₄)₂-H₂O (сингеніт) на основі дисперсії двопроменезаломлення Δn(ω).Отримані спектри Δk(ω') проаналізовано для кількох температур в області 293-450 K для механічно ненапружених і одновісно стиснутих (σ = 250 бар) зразків.